Has the fall in oil prices shifted the healthcare spending burden from the Organization of the Petroleum Exporting Countries' governments onto private spending? - Salem Al Mustanyir (Cogent Business & Management, 2022)
The OPEC countries rely on oil to fund their budgets, similar to many countries worldwide. However, the fall in oil prices in 2008 and 2014 put significant strain on their public finances, including healthcare finances. This study examines the effect of the fall in oil prices on OPEC countries' healthcare spending and whether the burden has shifted from government to private spending. The government and private healthcare spending after 2008 and after 2014 were compared to spending before 2008. Moreover, Welch's t-test was used to assess the difference between healthcare spending in the stated periods. The study found that the majority of OPEC countries decreased government healthcare spending after 2008 and after 2014, indicating that the burden shifted from governments to private spending. The study suggests that countries should minimize reliance on oil, diversify their income, and avoid relying heavily on debt and foreign reserves, as these might negatively impact healthcare spending in the future.
Keywords: H51; H61; H72; H75; I18; 650; fall in oil prices; financing challenges; Healthcare spending; OPEC countries